MORPHOGENESIS OF THE VASCULAR STRUCTURES OF THE GASTRIC WALL OF OFFSPRING BORN WITH DIABETES IN POSTNATAL ONTOGENESIS - Miyassar P. Abdaliyeva; Dilorom B. Adilbekova; Abdulaziz A. Akhrorov; Sardorjon S. Toshpulatov (Central Asian Journal of Medicine, 2025)
Maternal diabetes mellitus has a negative impact on the processes of growth, development and formation of internal organs in postnatal ontogenesis of offspring born from them. In the early postnatal ontogenesis of offspring, inflammatory-reactive and dystrophic changes are observed in the tissues and blood vessels of the stomach wall. These processes lead to developmental lag in the tissues and blood vessels of the stomach in the late stages of postnatal ontogenesis of offspring, the development of pathomorphological changes such as necrobiosis, atrophy and sclerosis.